Artificial Intelligence and Intellectual Properties: Legal and Ethical Considerations - Abdallah, Mohammad; Salah, Mousa (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This research delves into the intricate nexus of artificial intelligence (AI) and intellectual property (IP), addressing the pressing legal and ethical challenges in this evolving landscape. AI’s capacity to autonomously generate content and inventions raises pivotal questions about inventorship, copyright, and data privacy. It explores the ethical dimensions, considering algorithmic bias and fair usage in AI-generated content. The study emphasizes the urgent need for adaptable legal frameworks and standardized licensing agreements to accommodate AI’s role in innovation and content creation. Furthermore, it advocates for global harmonization of IP laws and ethical AI development. By offering practical recommendations for policymakers, AI developers, and stakeholders, this research aims to bridge the gap between AI innovation and IP protection, nurturing a future where ethical considerations and equitable IP rights coalesce in the AI era.